Size and unpredictable movement together affect the effectiveness of dynamic flash coloration. (April 2020) - Murali, Gopal; Kodandaramaiah, Ullasa
Abstract : Many animals have colour patterns that appear to change dynamically when the animal moves. Experiments have suggested that such colour patterns, termed 'dynamic flash' coloration, can reduce predatory attacks by misrepresenting the prey's location. However, the conditions that make this coloration effective are not known. We here tested the influence of two factors, target size and unpredictable movement, on the efficacy of dynamic flash coloration. Both these factors have independently been shown to affect the predator's ability to attack a moving prey accurately, but whether they interact with prey coloration remains unclear. Using a virtual predation experiment with human participants, we found that the effectiveness of dynamic flash coloration, when compared to background-matching coloration, declined as the size of the target increased, but only when the target movement was linear (i.e. predictable). However, when the movement was unpredictable (i.e. when the target adopted a 'protean' motion), we found dynamic flash coloration to be effective in reducing the number and accuracy of attacks irrespective of target size. Under most conditions, the effectiveness of dynamic flash coloration did not differ from that of a uniform luminance-matched grey target. Our results suggest that the efficacy of dynamic flash coloration is limited by prey size, but animals can overcome this constraint by employing an unpredictable movement trajectory. The study also provides direct empirical evidence that protean antipredator behaviour influences the effectiveness of prey coloration that works in motion. Highlights: Dynamic change in prey colour during motion may reduce predatory attacks. We tested the factors affecting the effectiveness of dynamic coloration. When movement was linear, dynamic coloration was effective only in small targets. It was effective irrespective of size when the movement path was unpredictable. Its evolution might be affected by prey size and escape trajectory.